A simple model of time zone differences, virtual trade and informality. Issue 1 (29th June 2020) - Mandal, Biswajit; Prasad, Alaka Shree
Abstract : Purpose: This paper aims to strive to model virtual trade resulting from time zone differences in an otherwise Heckscher–Ohlin set up which is absent in the literature. So, the paper adds some value to the existing literature on time zones (TZ) and trade. Design/methodology/approach: A competitive general equilibrium model is developed first to capture the effect of TZ differences on virtual trade. Then the authors examine, in brief, if distance can be accommodated in such framework. Finally, the authors extend the model to incorporate informality. Findings: It is seen that exploitation of time zone difference benefits skilled labor and hurts capital under reasonable assumption. In what follows, time zone difference exploiting sector expands, whereas the other sector contracts. Then, the model has been extended to examine how distance may also lead to similar outcomes. In addition, the model is further modified to explore the effect of virtual trade in an informality and associated extortion ridden economy. Interestingly, virtual trade turns out to be beneficial to unskilled workers as well, and leads to a fall in the number of extortionists, though informal production is augmented. Research limitations/implications: This model is a competitive model that may not clearly reflect the realistic world. However, interestingly this may form the basis of looking into some other appealing dimensions of the real world. Originality/value: TZ and related communication-cost-driven trade arguments are relatively less explored theoretically. Therefore, the work adds some value to the theoretical understanding of outsourcing in service trade that uses day-night differences across the globe.